Analysis of differentiated learning implementation in elementary schools during the 2020-2024 period - Sulistiani, Erna; Rokhman, Fathur; Pramono, Suwito Eko; Subali, Bambang; Widiarti, Nuni (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
Differentiated learning is a learning strategy that emphasizes the importance of the process of adjusting learning strategies that can meet the needs of each student with various ability backgrounds, especially in Elementary Schools. Differentiated learning recognizes that each student has a different learning style, learning speed, and interests. At the elementary school level, where students are actively developing their various abilities and potentials, this approach is very important to implement so that it can ensure that each student can learn optimally and achieve their best potential. This study aims to review various existing literature on the effect of implementing differentiated learning in elementary schools for the 2020-2024 period by analyzing 10 articles that have been published in relevant journals using Harzing's Publish or Perish and Google Scholar applications. Each article was analyzed and the results of the analysis were arranged in a table that included the title, author's name, year of publication, and research findings. The results of the analysis showed that differentiated learning was able to increase participation motivation and student learning outcomes with quite significant results compared to learning with conventional methods. This can be seen from several studies that show an increase in cognitive abilities and student learning outcomes. This study recommends ongoing training for teachers related to the implementation of differentiated learning with effective and efficient time management, as well as collaboration between all parties such as parents and learning communities, as well as the use of technology as an integral part of efforts to create a more inclusive and student-centered learning environment, especially in elementary schools.